Anesthesia Management in Neonates with Esophageal Atresia and Tracheoesophageal Fistula Repair: A Case Report - Manurung, Agus Suharto; Santoso, Kohar Hari (South Eastern European Journal of Public Health, 2024)
Introduction: Esophageal atresia with tracheoesophageal fistula (EA-TEF) requires complex anesthesia management due to challenges in airway control and the risk of complications. This study reports an 11-day-old neonate with distal EA-TEF which would conduct the repair surger. Case presentation: This study reports on an 11-day-old neonate, weighing 2.4 kg, admitted to Dr. Soetomo General Hospital due to continuous drooling shortly after birth. The initial examination indicated an inability to pass an orogastric tube, with no evidence of fever, respiratory distress, or hematin present. A diagnosis of esophageal atresia with tracheoesophageal fistula, associated with VACTERL abnormalities, was confirmed through radiological imaging showing respiratory distress syndrome and dilated bowel gas. This condition supported with increasing white blood cells level. General anesthesia was administered for surgical repair, and the patient’s hemodynamics and oxygen level remained unstable during the procedure. Discussion: Esophageal atresia with tracheoesophageal fistula (EA-TEF) requires timely surgical correction, but delays can lead to complications like aspiration pneumonia, as seen in this 11-day-old neonate with associated VACTERL abnormalities. General anesthesia was used with close monitoring to prevent gastric distension and maintain oxygenation. Hemodynamic instability and fluctuating oxygen saturation posed challenges during surgery, but the patient was successfully stabilized postoperatively, emphasizing the importance of precise anesthetic and surgical management in neonates with EA-TEF. Conclusion: Repairing AE-TEF presents challenges in airway management, hemodynamics, and oxygenation. Careful preoperative assessment, correct endotracheal tube placement, and controlled ventilation are essential for positive outcomes and minimizing complications in neonates undergoing TEF repair.